Impact of the 2017 ACC/AHA guideline on the prevalence of elevated blood pressure and hypertension: a cross-sectional analysis of 10 799 individuals. Issue 12 (31st December 2020) - Alyabsi, Mesnad; Gaid, Reham; Alqunaibet, Ada; Alaskar, Ahmed; Mahmud, Azra; Alghamdi, Jahad
Abstract : Objectives: To assess the effect of the 2017 American College of Cardiology and the American Heart Association (ACC/AHA) hypertension guideline on the prevalence of elevated blood pressure (BP) and hypertension and the initiation of antihypertensive treatment, as well as the level of adherence to the BP target in the Saudi population. Design: A cross-sectional study. Participants: A total of 10 799 adults (≥18 years old), with three BP readings during 2017–2020 from the Saudi Biobank was used. Primary outcome: Hypertension was defined using three sources: the Joint National Committee 7 Blood Pressure Guideline (JNC-7) guideline (systolic BP (SBP)≥140 or diastolic BP (DBP)≥90 mm Hg), the 2017 ACC/AHA guideline (SBP≥130 or DBP≥80 mm Hg) and a self-reported hypertension diagnosis. Results: The prevalence of hypertension, according to the JNC-7 guideline, was 14.49% (95% CI 14.37 to 14.61), and the 2017 ACC/AHA, 40.77% (95% CI 40.60 to 40.94), a difference of 26.28%. Antihypertensive medication was recommended for 24.84% (95% CI 24.69 to 24.98) based on the JNC-7 guideline and 27.67% (95% CI 27.52 to 27.82) using the 2017 ACC/AHA guideline. Lifestyle modification was recommended for 13.10% (95% CI 12.47 to 13.74) of patients with hypertension who were not eligible for a pharmacological intervention, based on the 2017 ACA/AHA guideline. For patients with prescribed antihypertensive medication, 49.56% (95% CI 45.50 to 53.64) and 27.81% (95% CI 24.31 to 31.59) presented with a BP reading above the treatment goal, based on the 2017 ACA/AHA and JNC-7 guidelines, respectively. Using the two definitions, the risk factors were older age, male gender, diabetes diagnosis, increased body mass index, waist circumference and waist-to-hip ratio. Conclusions: According to the 2017 ACC/AHA guideline, the prevalence of hypertension has increased significantly, but there was only a small increase in the proportion of patients recommended for antihypertensive treatment. A large proportion of patients with prescribed antihypertensive medication, had a BP above the target. Unless public health prevention efforts are adopted, the increased prevalence of elevated BP and hypertension will increase cardiovascular disease.